Manipulation of emergent vortices in swarms of magnetic rollers - Gašper Kokot (Nature Portfolio, 2018)
Active systems utilize energy input to realize structural complexity and functional diversity. This work shows that magnetic colloidal rollers spontaneously self-organize into unconfined macroscopic vortices under a magnetic field, which can be used to transport inert particles across a flat surface.